A green convergent paired electrochemical synthesis of 6H-pyrrolo[3, 2, 1-de]phenazin-1-amine derivatives and their antibacterial evaluation. (1st October 2016) - Sharafi-Kolkeshvandi, Mahnaz; Nematollahi, Davood; Nikpour, Farzad; Dadpou, Bita; Alizadeh, Hojjat
Graphical abstract: A green paired electrochemical synthesis of some antibacterial active 6 H -pyrrolo[3, 2, 1-de]phenazin-1-amine and 2-amino-1-phenyl-5-(( E )- (( E )-4-(phenylimino)cyclohexa-2, 5-dien-1-ylidene)amino)-1 H -indole-3-carbonitrile derivatives was carried out by anodic oxidation of 2-aminodiphenylamine and 4-aminodiphenylamine in the presence of nitrile derivatives as nucleophiles. Highlights: Electrochemical synthesis of 6 H -pyrrolo[3, 2, 1-de]phenazin-1-amine and 2-amino-1-phenyl-5-(( E )-(( E )-4-(phenylimino)cyclohexa-2, 5-dien-1-ylidene)amino)-1 H -indole-3-carbonitrile. Electrochemical oxidation of 2-aminodiphenylamine and 4-aminodiphenylamine in the presence of nitrile derivatives. antimicrobial activity of arylsulfonyl-4, 4'-biphenol derivatives. Observed homogeneous rate constant of the reaction of 4, 4′-diphenoquinone with arylsulfinic acids Abstract: A green paired electrochemical synthesis of some 6 H -pyrrolo[3, 2, 1-de]phenazin-1-amine and 2-amino-1-phenyl-5-(( E )-(( E )-4-(phenylimino)cyclohexa-2, 5-dien-1-ylidene)amino)-1 H -indole-3-carbonitrile was carried out by anodic oxidation of 2-aminodiphenylamine and 4-aminodiphenylamine in the presence of nitrile derivatives as nucleophiles. In addition, the synthesized compounds were evaluated for theirs in vitro antibacterial activity against four bacterial ATCC strains ( Bacillus cereus, Staphylococcus aureus, Escherichia coli, Shigell asonei ).